Nada será como antes? as transformações no Jornal Nacional - Arrebola, Talita Lima Chechin Camacho (2018)
The objective of this work is to analyze the hybrid communication strategies of the voice and the presence of the journalists in the presentation of the Jornal Nacional da Rede Globo through the processes of hybridization of languages, starting from the changes occurred on April 27, 2015, in relevant sections. As hypothesis of this research it is believed that the change in the communicational device of the voice and the presence of the presenters invites the public to the proximity and bond. However, the changes in the communicational processes did not promote substantial changes in the discursive plan of the telejournalism. If, on the one hand, they allowed the opening of a polysemic sense to the body and the voice of the communicators, on the other hand, it is not enough for an effective re-signification in the telejournalism presentation, since the relations between the voice and the presence are the extreme ends in the processes of hybridization of this new proposal of presentation of the Jornal Nacional. For this, the study is based on the theory of the authors Arlindo Machado, Beatriz Becker, Yvana Fechine, Norval Baitello Junior and Paul Zumtor, as well as on the analysis instrument related to the critical approach of extremities of Christine Mello, which consists in observe an audiovisual product analyzing it, from three procedures: deconstruction, contamination and sharing. With the changes in the presentation of the Jornal Nacional, professionals began to value the presence of the body, in addition to reinventing itself with emerging technologies, maintaining or re-establishing the bond with its public